Analysing Science Textbooks in Terms of Inquiry Levels of Activities and The Nature of Scientific Inquiry - Erdaş Kartal, Eda; Karabaş, Yasemin; Kaya, Eda Nur; Hartamacı, Samet (Erzincan University Journal of Education Faculty, 2024)
Textbooks are one of the main elements determining student experiences during science classes.The importance of textbooks in gaining the knowledge (nature of scientific inquiry) and the skills needed in scientific inquiry (SI) cannot be denied. This research aims to analyze science textbooks in terms of inquiry levels of activities and the nature of scientific inquiry (NOSI). Document analysis was used as the research method. A descriptive analysis technique is used to analyze the data. The textbooks were analyzed regarding the level of inclusion of NOSI themes using a framework developed by the researchers. The inquiry levels of the activities, which are thought to be inquiry activities, were determined according to the classification suggested by Rezba et al. (1999). It is found that some of the NOSI aspects are not included in the textbooks. Some expressions were found in textbooks that may cause misconceptions in students. It is concluded that the activities considered scientific inquiry are mainly at the confirmation level and the structured level.
Keywords: Döküman analizi; bilimsel sorgulamanın doğası; sorgulama düzeyleri; fen ders kitapları; Science Education; Fen Bilgisi Eğitimi; Document analysis; nature of scientific inquiry; inquiry levels; science textbooks; 4. Education; 10. No inequality